ANALISIS KESIAPAN GURU DALAM MENGHADAPI KURIKULUM MERDEKA MATA PELAJARAN IPAS KELAS IV - Allutfia, Fadila Ti; Setyaningsih, Maryanti (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to analyze and determine the readiness of teachers in facing the independent curriculum and preparation in delivering science and technology material in class IV. The subjects of this study were homeroom teachers for class IV with a sample of 3 teachers at SDN Bekasi Jaya IV, SDN Bekasi Jaya V and SDN Margahayu XIX Bekasi. The method used in this writing is descriptive qualitative method. To collect data, researchers conducted observations, interviews and documentation. In preparing the Independent Curriculum, teachers are required to attend seminars or workshops, seeking information on how to apply the Independent Curriculum so that they can properly apply the curriculum during the learning process. has the responsibility of holding special training for teachers so that teachers can prepare lessons in accordance with the independent curriculum policy. The school principal also needs to routinely monitor deficiencies so that they can be used as evaluation material.